Analysis of the Influence of Tourist Visits and Hotel Occupancy Rate on Labor Absorption in West Nusa Tenggara Province - Syafinah, Shofyah; Salmah, Emi; Masrun, Masrun (Westscience Press, 2024)
This study aims to analyze